2016
DOI: 10.1080/15548627.2015.1136769
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles restore lysosomal acidification defects: Implications for Parkinson and other lysosomal-related diseases

Abstract: Lysosomal impairment causes lysosomal storage disorders (LSD) and is involved in pathogenesis of neurodegenerative diseases, notably Parkinson disease (PD). Strategies enhancing or restoring lysosomalmediated degradation thus appear as tantalizing disease-modifying therapeutics. Here we demonstrate that poly(DL-lactide-co-glycolide) (PLGA) acidic nanoparticles (aNP) restore impaired lysosomal function in a series of toxin and genetic cellular models of PD, i.e. ATP13A2-mutant or depleted cells or glucocerebros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
172
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(180 citation statements)
references
References 50 publications
7
172
0
1
Order By: Relevance
“…This phenomenon can also limit the delivery of therapeutic nanoparticles to the intracellular target site. Nanoparticles depending on its physicochemical nature can alter the function of lysosome and subsequently favor the activation or the inhibition of autophagy [64][65][66]. For instance, we have observed that ZnO nanoparticles induce a loss of lysosome membrane integrity in BV2 cells at high-dose exposure (80 mg/mL) as seen by flow cytometry detection of acridine orange (Figure 2).…”
Section: Effect Of Nanoparticles On the Lysosomementioning
confidence: 79%
“…This phenomenon can also limit the delivery of therapeutic nanoparticles to the intracellular target site. Nanoparticles depending on its physicochemical nature can alter the function of lysosome and subsequently favor the activation or the inhibition of autophagy [64][65][66]. For instance, we have observed that ZnO nanoparticles induce a loss of lysosome membrane integrity in BV2 cells at high-dose exposure (80 mg/mL) as seen by flow cytometry detection of acridine orange (Figure 2).…”
Section: Effect Of Nanoparticles On the Lysosomementioning
confidence: 79%
“…ATP13A2 may protect against toxicity of α-syn by promoting its lysosomal clearance (Gitler et al, 2009; Usenovic et al, 2012). Loss of ATP13A2 causes impaired lysosomal acidification and reduced lysosomal proteolysis (Dehay et al, 2012b), while increased lysosomal pH is observed in fibroblasts from PD patients with ATP13A2 mutations (Bourdenx et al, 2016). …”
Section: V-atpase –Related Lysosomal Acidification Failure In Diseasementioning
confidence: 99%
“…Mutations in glucocerebrosidase (GBA), which can be associated with either PD or Gaucher Disease (an LSD), also impair lysosomal function, as GBA is a lysosomal enzyme essential for processing of substrates (Mazzulli et al, 2011). Additionally lysosomal de-acidification has been observed in human fibroblasts from PD patients with GBA mutations (Bourdenx et al, 2016). …”
Section: V-atpase –Related Lysosomal Acidification Failure In Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…This figure was originated from Deng et al [78] with permission were exposed to Trichloroethylene (TCE), one kind of solvents, they showed the nigrostriatal degeneration, the onset of parkinsonian features, a loss of nigral dopaminergic neurons and increased nigral accumulation of α-syn [108,109]. Now, nanoparticles (NPs) have been used as new approaches for the treatment of PD [110,111]. However, in some conditions, the NPs can induce the adverse effect on the DA neurons and may accelerate the development of PD possibly through decreasing DA concentration and TH levels, increasing oxidative stress, changing mitochondrial metabolism, inhibiting cell proliferation and enhancing cell apoptosis [112][113][114].…”
Section: α-Synuclein Aggregation and Parkinson Diseasementioning
confidence: 99%